PERCEPTIONS OF STUDENTS ON PROFESSIONAL ETHICS AMONG ACADEMIC STAFF IN SOUTH EASTERN NIGERIAN UNIVERSITIES - Uduma, Ulu Eke (African Journal of Social and Behavioural Sciences, 2025)
The study assessed perceptions of students on professional ethics among academic staff in southeastern Nigerian universities. The study adopted a cross-sectional survey design. The study population was drawn from federal, state, and private universities in the Southern zone of Nigeria to ensure fair representation. The study involved 60 students in FGDs across federal, state, and private universities in South Eastern Nigeria. The Focus Group Discussion (FGD) methodology was employed as a primary instrument for data collection in this study. Audio recordings were utilized to capture the participants’ contributions accurately, which were subsequently transcribed for analysis. The study revealed prevalent lapses in ethical conduct, with students highlighting issues of extortion and lack of accountability. The study also indicated that the incidence of unethical situations is the responsibility of all stakeholders. Policymakers like the National Universities Commission (NUC) and the federal and state ministries of Education will find this study useful when formulating policies relating to academics in the university. The study recommended that the government ensure strict adherence or conformity with professional ethics.